Application of Hybrid Real Time Simulator for solution of Smart Grid tasks on the example of Elgaugol energy cluster pilot project; IFOST 2012; Vol. 2 - Borovikov Y. S. Yuri Sergeevich (2012, 2012)
This paper describes hardware and functional features of Hybrid Real Time Simulator (HRTSim) of electrical power systems, also its application for solution of Smart Grid (SG) tasks concerned with active adaptive networks (AAN) construction. As an example of such task solution the working results of HRTSim implementation and its application for testing and setting up of active-adaptive voltage and var control system (AAVVCS) of regional Smart Grid are presented.